Mosses and liverworts show contrasting elevational distribution patterns in an oceanic island (Terceira, Azores): the influence of climate and space. (2nd July 2016) - Henriques, Débora S. G.; Borges, Paulo A. V.; Ah-Peng, Claudine; Gabriel, Rosalina
Abstract : Due to ongoing global changes, it is essential to establish a baseline record from which to determine future shifts in species distributions and community assembly patterns. In this context, we used digitised historical bryophyte distribution data along a 1021 m elevational gradient in Terceira Island (Azores) to determine how bryophyte species distribution varies with elevation and which spatial and climatic drivers contribute to this variation. We used ordinary least squares analysis to test for climatic and spatial data as explanatory variables for bryophyte richness and Mid-Domain Null simulations to assess the influence of spatial constraints on species distributions. Bryophyte richness follows a hump-shaped pattern, with mosses predominating in the first half of the gradient and liverworts in the second half. While moss richness did not correlate to any climatic variables and responded weakly to the presence of forest cover, liverwort presence was related to temperature, rainfall, humidity and the occurrence of native forest areas, suggesting that these plants are more sensitive to changes in their environment and can thus be used as better indicator species for climate change. Despite their inherent biases, our study shows that historically compiled data can be a valuable tool for preliminary assessment of macroecological patterns.